2016
DOI: 10.3390/ijms17111876
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Methylation Marker in Glioma Supporting Clinical Decisions

Abstract: The IDH1/2 gene mutations, ATRX loss/mutation, 1p/19q status, and MGMT promoter methylation are increasingly used as prognostic or predictive biomarkers of gliomas. However, the effect of their combination on radiation therapy outcome is discussable. Previously, we demonstrated that the IDH1 c.G395A; p.R132H mutation was associated with longer survival in grade II astrocytoma and GBM (Glioblastoma). Here we analyzed the MGMT promoter methylation status in patients with a known mutation status in codon 132 of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A combination of both IDH mutations and MGMT promoter methylation was associated with the best response rates to TMZ [ 33 , 36 ]. Moreover, Roszkowski et al found that patients with both MGMT promoter methylation and IDH1 mutations receiving radiotherapy had a better prognosis than those with MGMT methylation alone [ 150 ]. However, Vuong et al reported that not all GBM patients with methylated MGMT may benefit from TMZ, postulating that it is possible that only GBM patients mutated by TERT with MGMT methylation are sensitive [ 59 ].…”
Section: Mgmtmentioning
confidence: 99%
“…A combination of both IDH mutations and MGMT promoter methylation was associated with the best response rates to TMZ [ 33 , 36 ]. Moreover, Roszkowski et al found that patients with both MGMT promoter methylation and IDH1 mutations receiving radiotherapy had a better prognosis than those with MGMT methylation alone [ 150 ]. However, Vuong et al reported that not all GBM patients with methylated MGMT may benefit from TMZ, postulating that it is possible that only GBM patients mutated by TERT with MGMT methylation are sensitive [ 59 ].…”
Section: Mgmtmentioning
confidence: 99%
“…Although traditional histopathological methods are regarded as the gold standard for LGG classification, they do not adequately predict clinical outcome. Consequently, an increasing number of studies have shown that biomarkers may improve the clinical decision-making process (5). Hypermethylation of the O 6 -methylguanine-DNA methyltransferase promoter can effectively predict the responsiveness to temozolomide (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, unique expression and methylation patterns have been introduced in diagnostics as prognostic and predictive biomarkers. Since the best-known expression profiling performed 15 years ago in breast cancer (41), determination of the unique signature of gene expression (6,42) or promoter methylation is used more frequently, for example MGMT methylation in tumor tissue as a biomarker in glioma (43) or SEPT9 methylation in plasma as a biomarker in colorectal adenocarcinoma (44).…”
Section: Discussionmentioning
confidence: 99%
“…MGMT is an important glioblastoma prognostic and predictive biomarker in clinical use (43). Reports regarding prostate cancer are inconclusive (46,56,61).…”
Section: Discussionmentioning
confidence: 99%